Multiomic characterization, immunological and prognostic potential of SMAD3 in pan-cancer and validation in LIHC - Tao Zhou; Dan Dan Zhang; Jiejing jin; Jinyang Xie; Jianhua Yu; Chao Zhu; Rong Wan (Scientific Reports)
Abstract SMAD3, a protein-coding gene, assumes a pivotal role within the transforming growth factor-beta (TGF-β) signaling pathway. Notably, aberrant SMAD3 expression has been linked to various malignancies. Nevertheless, an extensive examination of the comprehensive pan-cancer impact on SMAD3’s diagnostic, prognostic, and immunological predictive utility has yet to be undertaken. Bioinformatics methods were employed to systematically investigate the potential carcinogenic impact of SMAD3. We extensively harnessed data from authoritative sources, including The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), cBioPortal, Human Protein Atlas (HPA), UALCAN, and various other databases. Our study encompassed a comprehensive analysis of the following aspects: differential SMAD3 expression and its association with prognosis across diverse cancer types, gene mutations, immune cell infiltration, single-cell sequencing analysis, DNA methylation patterns, and drug sensitivity profiles. In vitro experiments were conducted with the primary objective of appraising both the expression profile and the precise functional attributes of SMAD3 within the milieu of Liver Hepatocellular Carcinoma (LIHC). Our findings revealed significant variations in SMAD3 expression between cancerous and adjacent normal tissues. High levels of SMAD3 expression were consistently associated with unfavorable prognoses across multiple cancer types,. Additionally, our analysis of SMAD3 methylation patterns in human cancers unveiled a favorable prognosis linked to elevated DNA methylation levels in pan-cancer. Furthermore, we identified positive associations between SMAD3 expression and RNAm6A methylation-related genes in the majority of cancers. Moreover, SMAD3 expression displayed substantial correlations with immune cell infiltration. Notably, immune checkpoint genes exhibited significant associations with SMAD3 expression across diverse cancers. Single-cell sequencing results elucidated the pan-cancer single-cell expression landscape of SMAD3. Within specific cancer subtypes, SMAD3 expression exhibited a noteworthy positive association with distinctive facets of malignancy. Finally, in our comprehensive analysis of drug sensitivity, we discerned a catalog of prospective therapeutic agents. In our comprehensive analysis across multiple cancer types, we observed a significant disparity in SMAD3 expression compared to normal tissues, and this findings suggest that SMAD3 holds promise as both a prognostic biomarker and a therapeutic target against various cancers. Difference displayed a noteworthy association with patient prognosis.